Lesão variante de Maisonneuve com luxação tibiofibular proximal - Alencar Neto, Jonatas Brito (2019)
Maisonneuve injury is a rare entity accounting for 7% of all ankle fractures. One of its variants includes a proximal tibiofibular dislocation, which is an even more unusual injury. The present article reports a case of a 34-year-old male patient admitted to the emergency room with edema in the lower left limb after a sports trauma. An X-ray of the knee revealed anterolateral subluxation of the proximal tibiofibular joint, with no signs of fracture. After the evaluation of the member, the diagnosis of a lesion variant of Maisonneuve with proximal tibiofibular dislocation was confirmed. The authors describe this case, addressing clinical, radiological and surgical aspects of this variant.